2016
DOI: 10.21608/jfds.2016.43009
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Sensory Evaluation, Starter Activity and Rheological Properties of Cow and Coconut Milk

Abstract: The aims of this investigation were (1) to study the influence of mixing various levels of coconut milk to cow milk on the chemical composition, sensory evaluation and rheological properties, (2) to determine the activity of classic yoghurt and ABT cultures in the previously mentioned milk. Acidity, E h , total nitrogen and ash levels of cow milk were slightly higher than those of coconut milk. On the contrary, total solids and fat values highly raised in the coconut milk than in the cow milk. Coconut milk obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The Total Solids (TS) content in coconut milk was significantly (P<0.05) higher than those of soy, and cow milk respectively. The values reported in this study followed similar trend with those reported by [28] who revealed that considerable content of TS and fat was detected in coconut milk than in cow milk. Vitamin A was significant (P<0.05) among the three samples.…”
Section: Physicochemical Propertiessupporting
confidence: 91%
“…The Total Solids (TS) content in coconut milk was significantly (P<0.05) higher than those of soy, and cow milk respectively. The values reported in this study followed similar trend with those reported by [28] who revealed that considerable content of TS and fat was detected in coconut milk than in cow milk. Vitamin A was significant (P<0.05) among the three samples.…”
Section: Physicochemical Propertiessupporting
confidence: 91%
“…The data was analyzed according to [20], by programe of Statistical Package for the Social Sciences virision 20 (SPSS V.20) to study the effect of different treatments on the studied properties according to a complete random design (CRD), and the significant differences between the means were compared by the lowest significant difference (LSD).…”
Section: Discussionmentioning
confidence: 99%
“…Sensory characteristics of milk samples were evaluated by the staff of the Department of Food Sciences, College of Agricultural Engineering Sciences, University of Baghdad, the evaluation criteria and evaluated treatments were as shown in form A (table 1) which used by [20].…”
Section: Sensory Evaluation Of Milkmentioning
confidence: 99%
“…A nine-point Hedonic scale with one (1) representing "extremely dislike" and nine (9) "extremely like" was used. The qualities assessed were appearance, mouth fill, taste, flavor, and general acceptability [15].…”
Section: Sensory Evaluationmentioning
confidence: 99%